Stroke-like onset of brain stem degeneration presents with unique MRI sign and heterozygous NMNAT2 variant: a case report. Issue 1 (December 2016) - Schulz, Alexander; Wagner, Franziska; Ungelenk, Martin; Kurth, Ingo; Redecker, Christoph
Abstract Background Acute-onset neurodegenerative diseases in older patients are rare clinical cases, especially when the degeneration only affects specific regions of the nervous system. Several neurological disorders have been described in which the degeneration of brain parenchyma originates from and/or primarily affects the brain stem. Clinical diagnosis in these patients, however, is often complicated due to a poor understanding of these diseases and their underlying mechanisms. Case presentation In this manuscript we report on a 73-year-old female who had experienced a sudden onset of complex neurological symptoms that progressively worsened over a period of 2 years. Original evaluation had suggested a MRI-negative stroke as underlying pathogenesis. The combination of patient's medical history, clinical examination and exceptional pattern of brain stem degeneration presenting as "kissing swan sign" in MR imaging was strongly suggestive of acute onset of Alexander's disease. This leukoencephalopathy is caused byGFAP (glial fibrilary acidic protein) gene mutations and may present with brain stem atrophy and stroke-like onset of symptoms in elderly individuals. However, a pathognomonicGFAP gene mutation could not be identified by Sanger sequencing. Conclusions After an extended differential diagnosis and exclusion of other diseases, a definite diagnosis of the patient's condition presently remains elusive. However, whole-exome sequencing performed from patient's blood revealed 12 potentially disease-causative heterozygous variants, amongst which several have been associated with neurological disorders in vitro and in vivo – in particular the axon degeneration-relatedNMNAT2 gene.